Pengembangan pelatihan taktik menyerang berbasis media audio visual pada permainan bola tangan - Resha Avanza; Asep Angga Permadi; Z. Arifin; Mohd Izwan Shahril (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to evaluate the validity and feasibility of audiovisual media-based tactical training videos as a means of teaching handball tactics to coaches and athletes. The background to this issue stems from the difficulties experienced by coaches and athletes in understanding and applying tactics effectively during conventional training sessions. By utilising interactive audiovisual content, it is hoped that an improvement in tactical understanding can be achieved. Materials and methods. The research method is quantitative, with data collection through four techniques: observation of the video production and usage process, in-depth interviews with coaches and athletes, documentation of materials and training recordings, and distribution of questionnaires to three groups of respondents: media experts, subject matter experts (handball tactics), and athletes. The data obtained was then analysed using validation percentages to assess the feasibility and suitability of the content. Results. The validation results showed a score of 80% (‘Suitable’) from media experts, 83.33% (‘Very Suitable’) from material experts, and 83.54% (‘Very Suitable’) from athletes. The overall average score above 80% indicates that the video has a high level of validity and suitability. Conclusion. In conclusion, this audiovisual media-based tactical training video has been proven to be valid and feasible as a tactical learning medium in handball. The implementation of this medium is expected to enhance tactical understanding, facilitate the delivery of material, and support the effectiveness of training and athletes' performance in matches.